Hubungan Kejadian Hiperbilirubinemia dengan Inkompatibilitas ABO pada Bayi Baru Lahir di RSUD Abdul Moeloek Provinsi Lampung - Mentariasih Maulida; Ratna Dewi PS; Syazili Mustofa (Medula, 2021)
Bilirubin is a sequence product of red blood cells in the reticule-endothelial system. At excessive concentrations, about 5 mg/dL bilirubin will appear clinically as a yellow color on the skin and mucous membranes which is called jaundice. Jaundice can be physiological and pathological or commonly known as hyperbilirubinemia. Hyperbilirubinemia is a pathological condition that arises at the first day of birth and increasing of bilirubin levels 5 mg/dL per day rapidly, ABO incompatibility is the most common risk factor causes hyperbilirubinemia in newborns. ABO incompatibilities included in the main blood group antigen are blood group A and B which are the most common cases in newborns. This study aims to determine whether there is a relationship between incidences of hyperbilirubinemia with ABO incompatibility in newborns at Abdul Moeloek Hospital, Lampung. This is observational analytic study using cross sectional method. Total sampling method was done. Medical record was data source of this study. Data analysis was performed by chi-square test with p <0.05. The study used 325 medical records with 20% hyperbilirubinemia of newborn, 80% without hyperbilirubinemia, ABO incompatibility incidence is 20.9% and 79.1% without ABO incompatibility. Data analysis showed significant relationship of hipebilirubinemia with ABO incompatibility in newborns at Abdul Moeloek Hospital Lampung (p<0, 05). There study showed relationship between hypebilirubinemia with ABO incompatibility in newborn at Abdul Moeloek Hospital Lampung.